The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.3389/fneur.2011.00012
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Traumatic Brain Injury: A Behavioral, Proteomics, and Histological Study

Abstract: Psychological stress and traumatic brain injury (TBI) can both result in lasting neurobehavioral abnormalities. Post-traumatic stress disorder and blast induced TBI (bTBI) have become the most significant health issues in current military conflicts. Importantly, military bTBI virtually never occurs without stress. In this experiment, we assessed anxiety and spatial memory of rats at different time points after repeated exposure to stress alone or in combination with a single mild blast. At 2 months after injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
119
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 112 publications
(144 citation statements)
references
References 92 publications
20
119
4
Order By: Relevance
“…33 These studies have documented a variety of, at least, short-term effects, suggesting that blast can be associated with anxiety as well as impairments in a variety of learning and memory tasks. 5,26,31,34,36,43,47,49,50 One study also reported impairments in prepulse inhibition immediately after blast exposure, changes that had mostly recovered by 90 days after exposure. 38 We utilized a rat model of mTBI in which adult male rats were exposed to a controlled blast overpressure injury in a shock tube.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 These studies have documented a variety of, at least, short-term effects, suggesting that blast can be associated with anxiety as well as impairments in a variety of learning and memory tasks. 5,26,31,34,36,43,47,49,50 One study also reported impairments in prepulse inhibition immediately after blast exposure, changes that had mostly recovered by 90 days after exposure. 38 We utilized a rat model of mTBI in which adult male rats were exposed to a controlled blast overpressure injury in a shock tube.…”
Section: Discussionmentioning
confidence: 99%
“…23 Animals have been exposed to various forms of blast ranging from direct exposure to live explosives to controlled blast waves produced by compressed-air generators (reviewed in Elder et al 1 ) with activity in this area increasing dramatically in rodent models in recent years. 5, A number of studies have begun to look at the behavioral effects of blast across a range of blast exposures 5,26,31,33,34,36,38,43,[47][48][49][50] using blast alone or blast in combination with repeated stress 36 or other factors such as transportation or anesthesia. 33 These studies have documented a variety of, at least, short-term effects, suggesting that blast can be associated with anxiety as well as impairments in a variety of learning and memory tasks.…”
Section: Discussionmentioning
confidence: 99%
“…We maintained the air pressure in the water at 4 bar in order to have the least amount of water turbulence and to decrease the chance of exposing the fish to this stress factor. In mammals, stress resulted in a transient increase in anxiety, with no detectable brain tissue damage [54]. Hypoxia can lead to brain damage.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the observation that repeated mild injuries could result in chronic traumatic encephalopathy (CTE) (Lakis et al, 2013;Stein et al, 2014). has influenced scientists to start experimental projects on repeated mild blast induced TBI (Petraglia et al, 2014a,b;Glushakova et al, 2014;Goldstein et al, 2014).…”
Section: Clinicalmentioning
confidence: 99%
“…blast models that make use of rodents and pigs. Refined behavioral tests with a high sensitivity for stress reactions similar to posttraumatic stress will be important in the future work with blast Kovesdi et al, 2011;Kwon et al, 2011). Additional experiments are required to enable an understanding of the co-morbidity of TBI and PTSD.…”
mentioning
confidence: 99%